Pengaruh Pembelajaran Berbasis Masalah dengan Media Digital terhadap Kecakapan Berpikir Kritis pada Pelajaran Pendidikan Pancasila Kelas VIII MTsN 1 Treggalek - Arju Wijiono; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2025)
Education in the 21st century is required to improve 4C skills, especially critical thinking and problem solving in the era of globalization by utilizing technology in learning, such as digital media (websites and YouTube). With problem-based learning using digital media (websites and YouTube), it is expected that students can hone their critical thinking skills through discussion activities. This study aims to test whether or not there is an influence of problem-based learning with digital media on critical thinking skills in Pancasila Education lessons for class VIII MTsN 1 Trenggalek. The related theory is the constructivism learning theory by Lev Vygotsky, emphasizing the importance of the relationship between individuals and the social environment in forming knowledge. This study uses a quantitative method with a quasi-experimental design research type in the form of a nonequivalent control group design. The number of research samples was 64 students from class VIII who were divided into experimental groups and control groups and selected by cluster random sampling. Data were collected by means of tests, pre-tests and post-tests consisting of predetermined indicators, namely: interpretation, analysis, evaluation, conclusions, explanations, and self-regulation. Data analysis using non-parametric statistics, Mann-Whitney U test because the data obtained were not normally distributed and not homogeneous, by obtaining a significance value (2-tailed) of 0.170 > 0.05. So Ha is accepted and Ho is rejected, it can be concluded that there is an influence of problem-based learning with digital media on critical thinking skills in Pancasila Education lessons for class VIII MTsN 1 Trenggalek.